2017
DOI: 10.1111/cei.13054
|View full text |Cite
|
Sign up to set email alerts
|

Lys63-polyubiquitination by the E3 ligase casitas B-lineage lymphoma-b (Cbl-b) modulates peripheral regulatory T cell tolerance in patients with systemic lupus erythematosus

Abstract: Summary T cells from systemic lupus erythematosus (SLE) patients display a wide array of anomalies in peripheral immune tolerance mechanisms. The role of ubiquitin ligases such as Cbl-b has been described recently in these phenomena. However, its role in resistance to suppression phenotype in SLE has not been characterized, which was the aim of the present study. Thirty SLE patients (20 with active disease and 10 with complete remission) and 30 age- and sex-matched healthy controls were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Deficiency in CBL-B protein expression, recently observed in patients with systemic lupus erythematosus (SLE), correlated with a decrease in K63 ubiquitination specifically in CD4 + CD25 + Tregs but not in CD4 + CD25 – effector T cells isolated from patients with SLE, suggesting that dysfunctional CBL-B associated with an aberrant K63-ubiquitination profile of Tregs from such patients contributes to impaired immunosuppression [ 49 ]. This is thought to be due to the ability of CBL-B to ubiquitinate the TCRζ chain to terminate anti-CD3/CD28 antibody-mediated TCR activation [ 49 ]. Additionally, phosphorylated STAT3 is increased in CD4 + CD25 + Tregs from patients with SLE, but not from healthy controls [ 49 ].…”
Section: K63 Ubiquitination In Immune Signalingmentioning
confidence: 99%
“…Deficiency in CBL-B protein expression, recently observed in patients with systemic lupus erythematosus (SLE), correlated with a decrease in K63 ubiquitination specifically in CD4 + CD25 + Tregs but not in CD4 + CD25 – effector T cells isolated from patients with SLE, suggesting that dysfunctional CBL-B associated with an aberrant K63-ubiquitination profile of Tregs from such patients contributes to impaired immunosuppression [ 49 ]. This is thought to be due to the ability of CBL-B to ubiquitinate the TCRζ chain to terminate anti-CD3/CD28 antibody-mediated TCR activation [ 49 ]. Additionally, phosphorylated STAT3 is increased in CD4 + CD25 + Tregs from patients with SLE, but not from healthy controls [ 49 ].…”
Section: K63 Ubiquitination In Immune Signalingmentioning
confidence: 99%
“…Mechanistically, reduction of KAP1 expression in Hep3B cells does not affect STAT3 nuclear translocation and DNA-binding activity, but resulted in enhanced nuclear accumulation of STAT3 phosphorylated on Ser727, a modification required for its maximal transcriptional activation [ 125 ]. STAT3 activation can also be regulated via the ubiquitin/proteasome-dependent degradation of STAT3 [ 69 , 126 , 127 ]. Tanaka et al reported that PDLIM2, a nuclear ubiquitin E3 ligase, binds to and degrades STAT3 in a proteasome-dependent manner in human embryonic kidney (HEK) 293T cells [ 65 ].…”
Section: Stat3-interacting Proteinsmentioning
confidence: 99%
“…Treg disorders in SLE patients are characterized by abnormal peripheral tolerance that has been linked to a deficiency in the E3 ubiquitin ligase Cbl-b [41], involved in the regulation of T cell receptor signaling, during the induction of peripheral tolerance. Interestingly SLE patients were also characterized by an altered pattern of K63 ubiquitinated proteins in Tregs, with a decreased expression of K63 ubiquitinated proteins, related to increased pSTAT-3 expression [42]. These processes could be responsible for the loss of Treg suppressive capacity in SLE patients.…”
Section: Lysine 63 Ubiquitylation and Adaptive Immune Responsementioning
confidence: 99%